Mercury handbook : chemistry, applications and environmental impact - Kozin, L. F. (Royal Society of Chemistry, 2013)
This book provides a thorough understanding of amalgam metallurgy which is essential for academics, industrialists and postgraduates working in relevant fields. Guaranteed to bring a wealth of information, this book will be a welcome addition to the literature.